The Effectiveness of Zakat Disbursement by Amil Zakat Institutions in Indonesia - Bahri, Efri Syamsul; Utama, Indra; Arif, Zainal; Zaedi, Muhamad; Salamun, Ade (Al Maal: Journal of Islamic Economics and Banking, 2021)
The Amil Zakat Institute (LAZ) is an institution licensed to assist the National Board of Zakat (Baznas) in collecting, distributing, and utilizing zakat. One of the main tasks of the LAZ is to distribute zakat to mustahiq in the Very Effective category. This study compares the effectiveness of zakat disbursement at the Amil Zakat institution. The effectiveness of the allocation-to-collection ratio (ACR) method was determined using Zakat core principles (ZCP). The objects used in this research are the financial statements of the National Zakat Institute, including LAZ IZI, LAZ Rumah Zakat, and LAZ Dewan Dakwah. Measurements were performed from 2015 to 2019. The results of the study found that the level of disbursement effectiveness from 2016 to 2019 was LAZ Dewan Dakwah (n=101% highly effective category), LAZ IZI (n=92% highly effective category) ), and LAZ Rumah Zakat (n=88% effective category). The implication is that the three LAZs have advantages in terms of their disbursement. Therefore, it is suggested to optimize the collection of zakat through LAZ. Therefore, the benefits of zakat are increasingly felt by mustahiq